Forest plantations in Costa Rica and Nicaragua: performance of species and preferences of farmers - Piotto, D.; Montagnini, F.; Kanninen, M.; Ugalde, L.; Viquez, E. (2004)
The area of forest plantations in the tropics worldwide is increasing as a response to the expansion of degraded lands. Rural farmers of many regions of the dry and humid areas are responding to government and other incentives, dedicating portions of their land to native and exotic tree plantations with varied uses and objectives.We evaluated the success of reforestation efforts in a dry region of Nicaragua and in a humid region of Costa Rica where reforestation has been promoted by the governments with local assistance of technical personnel and non-governmental organizations. In all farms, the survival, diameter at breast height (dbh), height, form, and health of the tree plantations were evaluated. In addition information regarding the farmer's preferences and characteristics of the farms and the farmers was gathered through a survey including socioeconomic and silvicultural aspects. In both countries farmers used more native than exotic species for reforestation. Farmers are willing to continue reforesting as long as they continue to receive government incentives. In Costa Rica the plantations had better silvicultural management than in Nicaragua. In Nicaragua the species preferred by farmers for their growth were Azadirachta indica, Caesalpinia eriostachys, Eucalyptus spp., Gliricidia sepium, Leucaena leucocephala, and Tectona grandis. In Costa Rica the preferred species for their growth were Cordia alliodora, Gmelina arborea, Terminalia amazonia, Tectona grandis, Vochysia guatemalensis, and Virola koschnyi. The implementation of incentive programs for reforestation was a key factor in encouraging the participation of small and medium farmers.